Retaining Indigenous Students in Tertiary Education: Lessons from the Griffith School of Environment - Howlett, Catherine; Seini, Monica; Matthews, Chris; Dillon, Bronwyn; Hauser, Vivian (The Australian Journal of Indigenous Education, 2008)
Abstract Low retention of Indigenous peoples in all Australian universities has been identified as a problematic issue by the Australian Federal government. Griffith University (GU), Queensland, Australia, provided funding to examine the factors affecting Indigenous retention in higher education, with the aim of developing innovative participation and retention strategies specifically for Indigenous students. This paper focuses on research conducted within the Griffith School of Environment that questioned the possible links between the provision of information to commencing Indigenous students and their retention. It essentially examines to what extent current university structures support Indigenous enrolments and retention, via the information they receive upon enrolling. From interviews conducted in an informal discussion format with currently enrolled Indigenous students in the Griffith School of Environment, critical deficiencies were identified in the information Indigenous students receive during the early transition phase of university entrance. A key finding of this study, and which is the subject of current research, was the support amongst the students for the development of an Indigenised curriculum in science as a strategy for improving the attraction and retention of Indigenous students. This paper details the research project and its findings.